Importance of hydrothermal vents in scavenging removal of 230Th in the Nansen Basin - Valk, O. (2019)
In this study we present dissolved and particulate 230Th and 232Th results, as well as particulate 234Th data, obtained as part of the GEOTRACES central Arctic Ocean sections GN04 (2015) and IPY11 (2007). Samples were analyzed following GEOTRACES methods and compared to previous results from 1991. We observe significant decreases in 230Th concentrations in the deep waters of the Nansen Basin. We ascribe this nonsteady state removal process to a variable release and scavenging of trace metals near an ultraslow spreading ridge. This finding demonstrates that hydrothermal scavenging in the deep‐sea may vary on annual time scales and highlights the importance of repeated GEOTRACES sections.